Pengaruh Struktur dan Komposisi Tegakan Terhadap Cadangan Karbon Tumbuhan Bawah di Hutan Desa Simorangkir Julu, Kabupaten Tapanuli Utara - Indra Alexander Saragih; Muhdi Muhdi; Kansih Sri Hartini (Program studi Kehutanan USU, 2016)
The utilization of forest which not offset by maintenance and care efforts will lead to the destruction of forests so that increase carbon levels in atmosphere. All components of the vegetation either trees, shrubs, lianas and epiphytes, groundcovers are carbon sink. However, the growth of groundcover very strongly influenced by the structure and composition of stands. Measurements of carbon groundcover in this village forest needs to determine the value of the importance of forests to be carbon sink as part of efforts to mitigate climate change in the North Tapanuli District. The purpose of this research was to analyze stand structure and composition and calculate groundcover carbon stocks in forest of Simorangkir Julu Village. Object of this research is the stand and groundcover in the forest of Simorangkir Julu Village. The method used is analysis of vegetation at the stands and groundcovers. Destructive sampling method were used to harvest groundcover in 2 m x 2 m sample plots for carbon analyze. Then, followed by analysis of effect the structure and composition stands to groundcover carbon. The results of this research indicate that there were 26 species of groundcover. Carbon stock of groundcover in salagundi stand is 4.93 tonnes/ ha, and in pine stand 4.88 tonnes/ ha. Based on statistical analysis of carbon stocks groundcover in pine stands and Salagundi stands not significantly different. Carbon stocks are more influenced by the diversity and density of groundcover, soil type, and environmental condition.Keywords: species, groundcover, stand, carbon